Serum and tissue markers in colorectal cancer: State of art. (March 2017) - Berretta, Massimiliano; Alessandrini, Lara; De Divitiis, Chiara; Nasti, Guglielmo; Lleshi, Arben; Di Francia, Raffaele; Facchini, Gaetano; Cavaliere, Carla; Buonerba, Carlo; Canzonieri, Vincenzo
Abstract: Colorectal cancer (CRC) represents one of the most commonly diagnosed cancers worldwide. It is the second leading cause of cancer death in Western Countries. In the last decade, the survival of patients with metastatic CRC has improved dramatically. Due to the advent of new drugs (irinotecan and oxaliplatin) and target therapies (i.e. bevacizumab, cetuximab, panitumab, aflibercept and regorafenib), the median overall survival has risen from about 12 mo in the mid nineties to 30 mo recently. Molecular studies have recently widened the opportunity for testing new possible markers, but actually, only few markers can be recommended for practical use in clinic. In the next future, the hope is to have a complete panel of clinical biomarkers to use in every setting of CRC disease, and at the same time: 1) to receive information about prognostic significance by their expression and 2) to be oriented in the choice of the adequate treatment. Moreover, molecular analyses have shown that the natural history of all CRCs is not the same. Individual patients with same stage tumors may have different long-term prognosis and response to therapy. In addition, some prognostic variables are likely to be more important than others. Here we review the role of serum and tissue markers according to the recently published English literature. This paper is an extension of the article "Biological and clinical markers in colorectal cancer: state of art" by Cappellani A published in Jan 2010.